(untitled) (Teaching and Learning Inquiry, 2025)
An increasing number of university faculty have become interested in alternative grading systems in recent years. While there is a growing body of research on such grading systems, implementation can be a challenge for instructors. Mastery-based testing is a grading system in which students learn from feedback and have multiple attempts to demonstrate proficiency in a written exam setting without penalty. Student exam scores are determined by the number of course learning outcomes successfully completed by the end of the course. Given that all other aspects of the course are left in place, this model can serve as a relatively simple entry point into alternative grading. We implemented mastery-based testing in three sections of a 16-week high-enrollment university linear algebra course and gathered data on student perceptions of and performance in this revised course. In this paper, we report on students’ descriptions of the benefits and drawbacks of this system, their beliefs about final grades in this course compared to other courses, and their self-reported study habits.